2019
DOI: 10.1097/psy.0000000000000711
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Objective Sleep and Ambulatory Blood Pressure in a Community Sample

Abstract: Objective: Epidemiologic data increasingly supports sleep as a determinant of cardiovascular disease risk. Fewer studies have investigated the mechanisms underlying this relationship using objective sleep assessment approaches. Therefore, the aim of this study was to examine associations between daily blood pressure and both objectively assessed sleep duration and efficiency.Methods: A diverse community sample of 300 men and women ages 21-70, enrolled in the North Texas Heart Study, participated in the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 62 publications
(68 reference statements)
0
34
0
2
Order By: Relevance
“…Each domain is given a score of 0 to 3 and then combined for a total score ranging from 0 to 21. Sleep quality is categorized into four groups as very good (PSQI score ≤4), fairly good (5)(6)(7)(8)(9), fairly bad (10)(11)(12)(13)(14) and very bad sleep (≥15). SDB is defined as a No-SAS score ≥8, 33 which is validated in the Chinese population.…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each domain is given a score of 0 to 3 and then combined for a total score ranging from 0 to 21. Sleep quality is categorized into four groups as very good (PSQI score ≤4), fairly good (5)(6)(7)(8)(9), fairly bad (10)(11)(12)(13)(14) and very bad sleep (≥15). SDB is defined as a No-SAS score ≥8, 33 which is validated in the Chinese population.…”
Section: Definitionsmentioning
confidence: 99%
“…Based on existing literature, only a few studies examined the effects of objectively and subjectively measured sleep quality on BP and yielded inconsistent results. Objectively assessed lower sleep duration and/or efficiency, and poor subjective sleep quality, are associated with higher 24-hour and diurnal systolic BP (SBP) and higher nocturnal BP in various adult community dwellers; [5][6][7][8] nonetheless other studies did not observe a significant association between subjective poor sleep quality and BP. 9,10 In terms of hypertension, current evidence fails to provide conclusive results.…”
Section: Introductionmentioning
confidence: 96%
“…[7][8][9][10] A growing number of studies investigated the role of objective sleep characteristics on cardiovascular disease and its risk factors based on polysomnography (PSG) and actigraphy. [11][12][13] Objective sleep characteristics such as sleep efficiency (SE), arousal index (ArI), the sleep fragmentation index, the percentage of rapid eye movement (REM sleep %), and the percentage of slow-wave sleep (SWS %) were found to be associated with cardiovascular disease and related risk factors, including hypertension, diabetes mellitus, and metabolic syndrome. [13][14][15][16][17] Von Kanel et al also showed that long wake after sleep onset (WASO) was associated with an increased risk of coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have demonstrated that older adults, rather than younger adults, report poor sleep quality [ 24 , 25 ]. Poor sleep quality has been associated with high ambulatory BP [ 11 ]. Although there was a high prevalence of self-reported poor sleep quality in our sample, the association between sleep duration and 24-h BP remained statistically significant even after adjustment for self-reported poor sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, most studies assessed sleep duration via self-report [ 6 , 8 ] which is subject to recall bias compared to objective methods like wrist actigraphy [ 10 ]. Only one study [ 11 ] examined objective sleep duration and ABP among adults, but did not report the association of 24-h BP with sleep. We therefore examined the association between objective sleep duration and 24-h BP in an adult multi-ethnic community sample.…”
Section: Introductionmentioning
confidence: 99%